Liquid chromatography method with tandem mass spectrometry and fluorescence detection for determination of inflammatory biomarkers in gingival crevicular fluid as a tool for diagnosis of periodontal disease - Vernerová, Andrea; Krčmová, Lenka Kujovská; Heneberk, Ondřej; Radochová, Vladimíra; Švec, František (Journal of pharmaceutical and biomedical analysis, 2022)
The new ultra-high performance liquid chromatography method with tandem mass spectrometry and fluorescence detection allowing fast, selective, and high-throughput analysis of neopterin, kynurenine, tryptophan, and creatinine in gingival crevicular fluid (GCF) has been optimized. Defining the pathophysiology of periodontal disease and identification of potential diagnostic test for active periodontitis remains a significant challenge in the field of oral disease diagnosis. Analysis of GCF provides a non-invasive means of evaluating the role of the host response in periodontal disease. In addition, the analysis of GCF provides an information about current inflammation level of sampled site/tooth. Determination of GCF inflammatory biomarkers such as neopterin, kynurenine, and tryptophan can contribute to diagnosis, evaluation of treatment, and progression of periodontal diseases such as gingivitis and periodontitis. The separation of target analytes was carried out using a column KinetexTM Polar C18 100 Å, (100 × 3.0 mm) packed with 2.6 μm core-shell particles applying an elution with a gradient formed from 0.2% aqueous formic acid and 90% aqueous acetonitrile. Kynurenine, tryptophan, and creatinine were detected using mass spectrometry with electrospray ionization to improve the sensitivity while neopterin was detected using fluorescence detection. The separation of these four substances was achieved after using a very simple sample preparation technique convenient for small amount of biological sample. Only less than 20 μL sample was needed and the separation was completed in 4 min. MS/MS analysis was performed using multiple reaction monitoring (MRM) under a positive ionization mode. Deuterium labeled internal standard was used for the more precise quantification. The lower limits of quantification (LLOQ) for target analytes were 0.50 × 10-3 μmol/L for neopterin, 0.10 μmol/L for kynurenine, and 0.20 μmol/L for tryptophan and creatinine. The within-run and between-run accuracy were in a range of 96.67-114.77% for all quality controls and LLOQ of all analytes. Matrix effect, extraction recovery, and stability testing have all been investigated. The method was tested with real-life samples using GCF collected from patients suffering from periodontitis and from healthy controls. Neopterin levels in patients were significantly higher (P = 0.020) than in healthy subjects and indicate good potential of this method for using in evaluation of periodontal pathogenesis and healing outcomes following a treatment.
Keywords: Gingival Crevicular Fluid; Chromatography, Liquid; parodontitida; lidé; Chromatography, High Pressure Liquid; tandemová hmotnostní spektrometrie; Biomarkers; chromatografie kapalinová; Humans; gingivální exsudát; biologické markery; Periodontitis; Tandem Mass Spectrometry; vysokoúčinná kapalinová chromatografie